PERSEPSI SISWA KELAS ENAM TERHADAP QUIZIZZ SEBAGAI MEDIA PEMBELAJARAN KEMAMPUAN TATA BAHASA DI BULELENG, BALI - Putu Milandari; Kadek Heni Oktarina Wisudayanti; Luh Putu Dewi Ariani (ELT in Focus, 2024)
Mastering English grammar plays a vital role in supporting students in using English properly. In order to facilitate students in learning English it is necessary to have learning media that meets the needs of students. One of the technology-based learning media used in learning English is Quizizz application. This study investigates the perceptions of sixth-grade students in Bulelelng, Bali regarding the use of Quizizz as a learning tool in teaching grammar. This research employed a qualitative design to explore how students perceive the use of Quizizz in enhancing their grammar skills. The data were gathered through observation, interviews, and documentation. The study revealed that students have a good perception to the use of Quizizz as learning medium on grammar skill. Quizizz is a medium that meets the needs and abilities of students as a better learning medium to be used in learning grammar. Practically, students have no difficulty in using Quizizz and hold a positive view of Quizizz as learning for grammar. They find it effective and suitable for their learning needs, contributing to improved engagement. Overall, integrating Quizizz into grammar instruction emerges as an innovative approach that enhances student motivation.